Kinetic Modeling and Reactor Optimization of n-Butane Oxidative Dehydrogenation to Butadiene with Temperature-Dependent Kinetics in a Heterogeneous Catalytic System - Asyifa Raudjatul Jannah; Rr. Nabila Nindya Mustika Prabaswari; Haura Nadhira Mahsa; Muhammad Salman Hakim (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Oxidative dehydrogenation (ODH) of n-butane is regarded as a promising alternative route for the efficient synthesis of 1,3-butadiene. This study proposes a temperature-dependent kinetic model formulated using a power-law approach and applies it to a plug flow reactor (PFR) simulation. The model incorporates consecutive dehydrogenation reactions along with competing side reactions, including cracking pathways. Simulation results indicate that the developed kinetic model adequately represents the reaction mechanism, as reflected by the formation of 1,3-butadiene as the primary product and hydrogen as a secondary product. An increase in operating temperature from 450 to 600 °C significantly enhances n-butane conversion and butadiene yield, achieving values of 0.8700 and 0.8690, respectively, while maintaining selectivity nearly equal to unity. This trend confirms that the reaction rates are predominantly governed by Arrhenius-type kinetics, where higher temperatures favor the main dehydrogenation reaction over undesired side reactions. In contrast, changes in reactor volume have a comparatively minor impact on performance, indicating a kinetically controlled system with limited sensitivity to residence time. Overall, the proposed kinetic framework provides a reliable basis for evaluating reactor performance and supports process optimization and design for efficient ODH-based butadiene production. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).